Two far South: the responses of South African and Southern Jews to Apartheid and Segregation in the 1950s and 1960s - Mendelsohn, Adam (Department of Historical Studies, 2025)
This dissertation uses the comparative historical method to compare and contrast the responses of Southern and South African Jews to apartheid and segregation in the 1950s and 1960s. It focuses on the interrelationship of the two communities with reform rabbis and international Jewish organizations. The dissertation argues that the nature of individual and institutional responses was significantly shaped by exposure to a set of factors common to the South and South Africa. The dissertation is thematic, employing a variety of case studies. The dissertation begins by examining the effect of frontier conditions on reform rabbis. The author argues that the dispersed reform pulpits prevalent in these two contexts, and the type of rabbi that they generally attracted, served to inhibit civil rights activism. Differential exposure to these conditions, together with the presence of various liberating features, determined the risks and opportunities that frontier rabbis encountered. Thereafter, the dissertation analyzes the interactions of the Southern and South African Jewish communities with northern-based national Jewish organizations (in the case of the former) and international Jewish organizations (in the case of the latter). The author compares the interplay of the Southern lodges of the B'nai B'rith with the Anti-Defamation League, and the interrelationship of the South African Jewish Board of Deputies with various overseas Jewish groups. Whereas in the first section, rabbinical responses in the South Africa and the South are analysed together, here the two communities are dealt with separately. The author argues that the responses of external organizations were shaped by pressure from constituencies in the South and South Africa. These pressures competed with other philosophical and political considerations in determining policy towards segregation and apartheid.